Impaired Glucose Metabolisms of Patients with Obstructive Sleep Apnea and Type 2 Diabetes - Ye Zhang; Yanpeng Xing; Haibo Yuan; Xiaokun Gang; Weiying Guo; Zhuo Li; Guixia Wang (Journal of Diabetes Research)
Aims. Obstructive sleep apnea (OSA) is a very common disorder which is associated with metabolic comorbidities. The aims of this study were to analyze clinical data of patients with OSA and evaluate influence of sleep-disordered breathing on glycometabolism and its underlying mechanisms. Methods. We designed a cross-sectional study involving 53 OSA patients in The First Hospital of Jilin University from March 2015 to March 2016. They underwent a full-night polysomnography, measurement of fasting blood glucose and blood lipid profiles. Besides, we chose 20 individuals with type 2 diabetes mellitus (T2DM) as a subgroup for an in-depth study. This group additionally underwent a steamed bread meal test and measurement of HbA1c, C-reactive protein, tumor necrosis factor-α, interleukin 6, morning plasma cortisol, and growth hormone. Results. The two groups which with or without T2DM showed no significant differences in baseline characteristics. As for OSA patients with T2DM, the severe OSA group had higher homeostasis model assessment of insulin resistance (HOMA-IR) (P=0.013) than the mild-to-moderate OSA group, whereas had lower morning plasma cortisol levels (P=0.005) than the mild-to-moderate OSA group. AHI was positive correlated with HOMA-IR (r=0.523, P=0.018), yet negative correlated with morning plasma cortisol (r=−0.694, P=0.001). However, nadir SpO2 was positive correlated with morning plasma cortisol (rs=0.646, P=0.002), while negative correlated with HOMA-IR (rs=−0.489, P=0.029). Conclusions. Our study showed that sleep-disordered breathing exerted negative influence on glucose metabolisms. The impairment of hypothalamic-pituitary-adrenal axis activity may be one of the underlying mechanisms of the glycometabolic dysfunctions in OSA with T2DM patients.